The Process Of Teaching Learning English Of The Second Semester Informatics Enginering Students Of Stmik Pelita Nusantara Medan - MERLIN Helentina Napitupulu (Jurnal Mantik Penusa, 2015)
This research deals with the classroom process during teaching learning English to the second semester informatics engineering students of STMIK Pelita Nusantara Medan. The objectives of this research are to know how English is taught in Informatics engineering of STMIK Pelita Nusantara Medan and want to know why it is done as the way it is. This research conducted qualitative method. The data were obtained from the observation and interview. The data collected were analyzed by applying interactive model of Miles and Huberman. The location of this research was STMIK Pelita Nusantara. The subject was English lecturer who taught ESP in second semester students of informatics engineering. The result of teaching ESP (English for Specific Purpose) was not suitable to develop the students’ competence in communicating English. Teaching ESP can be effective when the lecturer’s competence matches to teaching ESP. The data analysis showed that teaching structure and reading comprehension need both lecturer’s competence and students’ ability to make ESP teaching successful. The lecturer’s reasons in selecting materials, determining competence and also conducting the classroom process were based on her belief that they were suitable for the informatics engineering students. It is suggested to the lecturer to always update, revise and suit the teaching materials to find out the best strategy and media to develop teaching ESP for informatics engineering students.Key words: teaching learning English, ESP